2014
DOI: 10.1007/s11999-013-3308-9
|View full text |Cite
|
Sign up to set email alerts
|

Cemented versus Uncemented Hemiarthroplasty for Displaced Femoral Neck Fractures: 5-year Followup of a Randomized Trial

Abstract: Background Displaced femoral neck fractures usually are treated with hemiarthroplasty. However, the degree to which the design of the implant used (cemented or uncemented) affects the outcome is not known and may be therapeutically important. Questions/purposes In this randomized controlled trial, we sought to compare cemented with cementless fixation in bipolar hemiarthroplasties at 5 years in terms of (1) Harris hip scores; (2) femoral fractures; (3) overall health outcomes using the Barthel Index and EQ-5D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
162
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(176 citation statements)
references
References 22 publications
4
162
0
2
Order By: Relevance
“…A five year follow-up of a randomised trial with modern stems demonstrated a higher hip score for uncemented HA, but also increased risk of later femoral fractures [29]. Furthermore, two randomised controlled trials conducted by comparing modern uncemented and cemented stems concluded that both methods lead to equivalent functional results [14,21].…”
Section: Discussionmentioning
confidence: 99%
“…A five year follow-up of a randomised trial with modern stems demonstrated a higher hip score for uncemented HA, but also increased risk of later femoral fractures [29]. Furthermore, two randomised controlled trials conducted by comparing modern uncemented and cemented stems concluded that both methods lead to equivalent functional results [14,21].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that uncemented hemiarthroplasty leads to impaired mobility, induces more post-operative pain (Parker, Gurusamy & Azegami 2010, Li et al 2013, mechanical complications of the device (Yli-Kyyny et al 2014, Li et al 2013) and increased reoperation rates (Gjertsen et al 2012, Yli-Kyyny et al 2014 compared to cemented hemiarthroplasty. In contrast, a recent five-year followup study, randomized by surgical method after femoral neck fracture, reported better hip function measured by the Harris Hip Score for uncemented than for cemented hemiarthroplasty (Langslet et al 2013). Another randomized controlled trial for displaced femoral neck fractures reported better quality of life two years after bipolar hemiarthroplasty compared to unipolar hemiarthroplasty, but no differences were found in hip functioning, reoperation rates or mortality (Inngul et al 2013).…”
Section: Risk Factors For Hip Fracture 212mentioning
confidence: 99%
“…Both cemented and uncemented hemiarthroplasty have provided good results. (1)(2)(3)(4)(5) Earlier studies reported a higher risk of DVT in cemented TKR and THR. (6)(7)(8)(9)(10) Several studies have also demonstrated thrombogenic properties of bone cement that may contribute towards the development of DVT.…”
Section: Discussionmentioning
confidence: 99%
“…Both cemented and uncemented hemiarthroplasty have been used with good results; recent literature shows that both techniques lead to good functional outcomes and postoperative pain control, although some authors reported that uncemented hemiarthroplasty was associated with more implant-related complications. (1)(2)(3)(4)(5) In earlier studies reported in the 1990s, the cemented prosthesis was associated with a higher incidence of deep vein thrombosis (DVT) in total knee replacements (TKR) and total hip replacements (THR). (6)(7)(8)(9)(10) Subsequent studies, however, provided contradictory results and there was a lack of new data thereafter.…”
Section: Introductionmentioning
confidence: 99%